An Implementation of Project Investment Management on Blockchain-based Crowdfunding System - Yan Watequlis Syaifudin; salies Apriliyant; Hein Htet; Ferdy Hanan Pradana; Yuri Ariyanto; Indrazno Siradjuddin; Pramana Yoga Saputra; Triana Fatmawati (Asian Journal Science and Engineering, 2024)
This study explores the transformative impact of blockchain technology on corporate investment management by developing an application that enhances transparency, security, and efficiency while mitigating fraud risks. By utilizing the Proof of Authority (PoA) methodology on a private blockchain network, the application enables secure, immutable transaction records and facilitates the management of investment projects along with token purchase transactions. It is structured using the Waterfall model, including essential phases such as requirements analysis and rigorous testing, which demonstrate the application’s ability to improve operational efficiency and foster accountability among stakeholders. The research highlights the role of tokenization in crowdfunding, wherein rights or assets are converted into digital tokens, enhancing transparency and liquidity. The system also integrates smart contracts to automate critical investment processes while ensuring secure user authentication and authorization. Evaluations reveal high success rates in functionality and user acceptance, though challenges such as scalability and regulatory compliance remain. Addressing these aspects is vital for maintaining the system's effectiveness and user confidence in decentralized investment management.